THE INFLUENCE OF MANAGERIAL TEAM E-PROJECTS ON STUDENTS’ INDEPENDENT ATTITUDES - Budiarti, Retni S; Harlis, Harlis; Siburian, Jodion (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This study aims to evaluate the impact of the E-Project Managerial Team on fostering independence among Biology Education students at Universitas Jambi Faculty of Teacher Training and Education. The research investigates how managerial technology influences students' ability to manage tasks autonomously in an academic setting. Using a mixed-methods approach with an exploratory sequential design, the study combines quantitative data from questionnaires with qualitative insights. A random sampling method was applied to select participants from 143 students. Data analysis was conducted using IBM SPSS 24, employing descriptive statistics, normality, linearity, and regression tests to interpret the relationships between variables. The normality test returned a significance value of 0.614, while the linearity test showed a value of 0.482, confirming the appropriate distribution and relationships of the data. Results from the regression analysis (F value of 36.487, p = 0.001) revealed a statistically significant positive influence of the E-Project Managerial Team on students' independence. Descriptive analysis also indicated that while some students held neutral views, a considerable portion acknowledged improvements in their self-management and autonomy due to the team's involvement. This research uniquely integrates managerial technology with biology education, highlighting how digital project management tools can enhance student independence. It contributes to the growing literature on educational technology by offering innovative methods for promoting autonomy, time management, and individual skill development among students. This work provides practical insights for educators seeking to implement technological solutions to support self-directed learning.